2001
DOI: 10.1002/1097-0320(20011201)45:4<285::aid-cyto10018>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibody concentration on the separation of human natural killer cells in a commercial immunomagnetic separation system

Abstract: Background:The magnetic separation of a cell population based on cell surface markers is a critical step in many biological and clinical laboratories. In this study, the effect of antibody concentration on the separation of human natural killer cells in a commercial, immunomagnetic cell separation system was investigated. Methods: Specifically, the degree of saturation of antibody binding sites using a two-step antibody sandwich was quantified. The quantification of the first step, a primary anti-CD56-PE antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…The average magnetophoretic mobility of the targeted cells to achieve a 2.9 log 10 depletion was approximately 8 to 10 times higher than the mobility achieved when following the manufacturers recommended labeling protocol. Interestingly, as with the study by Comella et al (2001) reported above, the total recovery of the immunomagnetically targeted cells (sum of the CD3+ cells in the negative and positive eluent) significantly decreased from 90% when no immunomagnetic label was used to 51% when the targeted cells had the highest magnetophoretic mobility. Equally disturbing was the observation that the recovery of a non-targeted, spiked cell line (a CD34 expressing cell line) was only 60%, further indicating a non-specific loss of cells in the column.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The average magnetophoretic mobility of the targeted cells to achieve a 2.9 log 10 depletion was approximately 8 to 10 times higher than the mobility achieved when following the manufacturers recommended labeling protocol. Interestingly, as with the study by Comella et al (2001) reported above, the total recovery of the immunomagnetically targeted cells (sum of the CD3+ cells in the negative and positive eluent) significantly decreased from 90% when no immunomagnetic label was used to 51% when the targeted cells had the highest magnetophoretic mobility. Equally disturbing was the observation that the recovery of a non-targeted, spiked cell line (a CD34 expressing cell line) was only 60%, further indicating a non-specific loss of cells in the column.…”
Section: Introductionsupporting
confidence: 76%
“…In a number of previous publications, the importance of the relationship of the magnetophoretic mobility of immunomagnetically labeled cells to the performance of several magnetic cell separation systems was experimentally demonstrated (Comella et al 2001; Lara et al 2004; Tong et al 2007). In general, by making the targeted cells more magnetic, the cell separator performance, with some qualifications, improved.…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown the dependence of the magnetic labeling on the amount of bound primary antibody used in the immunomagnetic labeling complex. Thus, we have further validated CTV as an instrument useful for evaluation of magnetically conjugated antibodies and the related cell surface chemistries (14,20). The ability to standardize the magnetic labeling and thus predict cell behavior in a continuous flow, transport-based magnetic sorting system allows the operator to control the sorting parameters such as flow rates, for gating the cells according to their magnetophoretic mobility (13,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several attempts to develop immunotherapy, such as cytokine therapy, for the control of chronic HBV infection, and some results are promising. The LCMV mouse model has showed the essentiality of IL-2 administration timing and differentiation status in designing IL-2 therapy, indicating a therapeutic function for IL-2 [146]; TGF-β, which has been discussed for HBV immunotherapy, is produced by HBVspecific CD8 + T cells and contributes to CD8 + T-cell restoration [147][148][149][150]. As a main regulative cytokine of cellular immunity against viral infection, IL-10 possesses inhibitory effects on cell-mediated immune responses [151]; thus, its role in HBV treatment is under exploration.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%